Principal’s Transformational Leadership in Optimizing Learning Communities at SMA Negeri 1 Donorojo, Jepara Regency - Nela Veristika; Yovitha Yuliejantiningsih; Supriyono Purwosaputro (FKIP - Universitas Riau, 2026)
This study examines the role of the principal’s transformational leadership in optimizing the learning community as a medium for teachers’ professional development. Principals are expected to inspire, motivate, and empower teachers to foster a collaborative, reflective, and sustainable learning culture. This research aims to analyze the implementation of transformational leadership at SMA Negeri 1 Donorojo, Jepara Regency, focusing on four dimensions: inspirational motivation, idealized influence, intellectual stimulation, and individualized consideration. A qualitative phenomenological approach was employed to explore participants’ lived experiences. The study was conducted from September to October 2025, with data collected through observations, in-depth interviews, and documentation. Data analysis followed the stages of data collection, condensation, display, and conclusion drawing, while data validity was ensured through triangulation of sources, methods, and time. The findings indicate that the principal’s transformational leadership effectively optimizes the learning community. Inspirational motivation strengthens collaboration and collective commitment, idealized influence builds trust and professional ethics, intellectual stimulation promotes innovation and lifelong learning, and individualized consideration supports mentoring and personal development. The integration of these dimensions creates a collaborative, reflective, and sustainable learning community that enhances the quality of learning.